Pengaruh Lokasi, Persepsi Harga, Dan Citra Merek Terhadap Keputusan Pembelian Konsumen Mixue - NISA, KHOIRUN; Khalid, Jamaludin (Human Capital Development, 2024)
The aim of this study is to explore how location, price perception, and brand image influence consumers' decisions to buy Mixue products. It was conducted among Mixue product purchasers in March-April 2024 using a quantitative approach. Primary data was collected through a questionnaire using a accidental sampling, involving a total of 100 respondents. The data were subsequently analyzed using the method of analysis with a multiple linear regression model approach. The results suggest that consumers' perceptions of price and brand image affect their purchase decisions individually, whereas location does not. Overall, the study implies that all three factors collectively impact consumers' purchasing choices.